UWAGA!!! Ten kto prześle najszybciej prawidłowe zadanie oczyma -50p. Rozwiąż równanie: 3(x+2)²+(2x-1)²-7(x+3)(x-3) = 28 x-3/2+x = 4x-1/2-0,25(2x+3) x-3/2+x=4x-1/2-0,25(2x+3)

UWAGA!!! Ten kto prześle najszybciej prawidłowe zadanie oczyma -50p. Rozwiąż równanie: 3(x+2)²+(2x-1)²-7(x+3)(x-3) = 28 x-3/2+x = 4x-1/2-0,25(2x+3) x-3/2+x=4x-1/2-0,25(2x+3)
Odpowiedź

3(x+2)²+(2x-1)²-7(x+3)(x-3)=28 3(x²+4x +4) +2x² - 7(x²-9)=28 3x²+12x+12+2x²-7x²+63=28 -2x² + 12x + 63 = 28 -2x² + 12x= 35 /√ -2x + √12x = √35

3(x+2)²+(2x-1)²-7(x+3)(x-3) = 28 3(x²+4x+4)+4x²+1-7(x²-9)=28 3x²+12x+12+4x²+1-7x²+63=28 7x²-7x²+12x=28-12-1-63 12x= -48/12 x=-4 x-3 kreska ułamkowa2+x = 4x-1 kreska ułamkowa 2-0,25(2x+3) Mnożenie na krzyż (x-3)*2-0,25(2x+3)=(2+x)*(4x-1) (x-3)* (2-0,5x-0,75)=8x-2+4x²-2 (x-3)*(1,25-0,5x)=4x²+8x-4 1,25x-0,5x²-3,75+1,5x=4x²+8x-4 -4x²-0,5x²-8x+1,25x+1,5x= -4+3,75 -4,5x²-5,25x= -0,25

Dodaj swoją odpowiedź